2006
DOI: 10.1089/cap.2006.16.699
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Controlled Study of the Effects of Atomoxetine on Bladder Control in Children With Nocturnal Enuresis

Abstract: Compared with placebo, atomoxetine treatment was associated with a significant increase in dry nights in children with nocturnal enuresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…Recent studies, including a double-blind randomized placebo-controlled trial, have noted that atomoxetine, a medication that is approved for the treatment of ADHD, has been found to decrease frequency of bedwetting among children with enuresis with or without ADHD 51,52. Interestingly, an earlier study found that the presence of ADHD predicted worse outcome for treatment of enuresis with alarm, DDAVP, or imipramine 53.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, including a double-blind randomized placebo-controlled trial, have noted that atomoxetine, a medication that is approved for the treatment of ADHD, has been found to decrease frequency of bedwetting among children with enuresis with or without ADHD 51,52. Interestingly, an earlier study found that the presence of ADHD predicted worse outcome for treatment of enuresis with alarm, DDAVP, or imipramine 53.…”
Section: Discussionmentioning
confidence: 99%
“…History of fecal incontinence was negative after toilet training. The patient's enuresis was unresponsive to multiple trials of pharmacologic agents, with evidence supporting their use for enuresis: Imipramine (Glazener et al 2003) up to 2 mg/kg for 6 weeks, desmopressin (Glazener and Evans 2002) in doses up to 40 lg as nasal spray as well as 0.4 mg orally plus a trial of atomoxetine (Sumner et al 2006). All had failed to produce even a single dry night.…”
Section: Case Reportmentioning
confidence: 99%
“…Conditions whose standard therapy has been shown to be no better than placebo e e.g. primary nocturnal enuresis [32]. 3.…”
Section: The Logic Of Clinical Purposementioning
confidence: 99%